=
(
−
2
y
)
(
2
)
+
6
y
−
1
+
−
1
(
(
−
4
y
)
(
2
)
−
3
y
+
9
)
=
(
−
2
y
)
(
2
)
+
6
y
+
−
1
+
−
1
(
(
−
4
y
)
(
2
)
)
+
−
1
(
−
3
y
)
+
(
−
1
)
(
9
)
=
(
−
2
y
)
(
2
)
+
6
y
+
−
1
+
8
y
+
3
y
+
−
9
=
−
4
y
+
6
y
+
−
1
+
8
y
+
3
y
+
−
9
Combine Like Terms:
=
−
4
y
+
6
y
+
−
1
+
8
y
+
3
y
+
−
9
=
(
−
4
y
+
6
y
+
8
y
+
3
y
)
+
(
−
1
+
−
9
)
=
13
y
+
−
10
Answer:
Perpendicular (A)
Step-by-step explanation:
First find the gradient of the first line:
Change in y/ Change in x = -7-(-2)/ -9-(-12) = -5/3
Now find the gradient of the second line:
9-6/1-6 = -3/-5 = 3/5
When we multiply the gradient of two perpendicular lines we will get:
m1 x m2 = -1
If we multiply 3/5 and -5/3 we will get -1
Therefore it is perpendicular!
The closest marks on the ruler that was used to make a measurement of 23.435m is 0.01m apart.
<h3>What is a Ruler?</h3>
This refers to a tool which is used to measure distances of two points or area and has standard markings.
Since the thousandth digit is uncertain and the significant figures are digits which are read from the measuring instrument plus one doubtful number on the ruler then the most appropriate choice will be 0.01m.
Read more about Ruler here brainly.com/question/18558504
#SPJ4
Write the problem. ...
Decide whether to use addition or subtraction to isolate the variable term. ...
Add or subtract the constant on both sides of the equation. ...
Eliminate the coefficient of the variable through division or multiplication. ...
Solve for the variable.
Answer:
the answer is C . (y-5)(y-5)
Step-by-step explanation:
i'm the same dude